Catalytic Properties and Immobilization Studies of Catalase from Malva sylvestris L. - G. Arabaci; A. Usluoglu (Journal of Chemistry)
Catalase was partially purified from Malva sylvestris L. and immobilized onto chitosan. Then, its catalytic properties were investigated. (NH4)2SO4 precipitation and dialysis were performed in the extracted enzyme. Further purification was performed with sephadex G-200 column. Kinetic studies of the purified enzyme activity were measured and characterized. The inhibitory effects of KCN, NaN3, CuSO4, and EDTA on M. sylvestris L. catalase activity were observed except NaCl. Furthermore, M. sylvestris L. catalase was immobilized covalently with glutaraldehyde onto chitosan particles. The pH and temperature optima as well as the changes in the kinetics (Km, Vmax) of the immobilized and free M. sylvestris L. catalase were determined. The Km value for immobilized catalase (23.4 mM) was higher than that of free enzyme (17.6 mM). Optimum temperature was observed higher than that of the free enzyme. The optimum pH was the same for both free and immobilized catalases (pH 7.50). Immobilized catalase showed higher storage and thermal stabilities than free catalases. Free catalase lost all its activity within 60 days whereas immobilized catalase lost 45% of its activity during the same incubation period at 4°C. The remaining immobilized catalase activity was about 70% after 8 cycles of batch operations.